2020
DOI: 10.3390/su12020554
|View full text |Cite
|
Sign up to set email alerts
|

Start Walking! How to Boost Sustainable Mode Choice—Psychological Measures to Support a Shift from Individual Car Use to More Sustainable Traffic Modes

Abstract: Transport is one of the sectors that contributes to global warming. To tackle this issue, one of the most important tasks is to enhance/support a mode shift from individual car use to more sustainable traffic modes. To achieve this, psychology-based measures are needed. We need to understand what keeps people from walking, and what motivates people who do walk to do so, or to define the barriers and the preconditions that are needed for walking or cycling. These preconditions are perceived in a different way b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
6
0
5
Order By: Relevance
“…The literature also shows that there must be an effort to change people's behavior, mainly through marketing and educative campaigns promoting the use of sustainable means of transport in the city [55]. There are campaigns to promote cycling to school and to work, like Bike to School Day or Bike2Work [56,57], public campaigns to raise car drivers' awareness to the presence of cyclists that teach them some techniques, like opening the door with the right hand when exiting a car, and also to raise awareness to the benefits of cycling in a city [27,58]; iii) debates, meetings, congresses, and forums about cycling and mobility are important to put the bicycle on the Agenda of cities [59]; iv) laws, street laws, and regulations must be revised in order to better protect the unarmed and more vulnerable road users and to make the people who are using vehicles with a higher probability of causing injury and death more accountable [60][61][62][63].…”
Section: Planning Cycling For a Sustainable Mobilitymentioning
confidence: 99%
“…The literature also shows that there must be an effort to change people's behavior, mainly through marketing and educative campaigns promoting the use of sustainable means of transport in the city [55]. There are campaigns to promote cycling to school and to work, like Bike to School Day or Bike2Work [56,57], public campaigns to raise car drivers' awareness to the presence of cyclists that teach them some techniques, like opening the door with the right hand when exiting a car, and also to raise awareness to the benefits of cycling in a city [27,58]; iii) debates, meetings, congresses, and forums about cycling and mobility are important to put the bicycle on the Agenda of cities [59]; iv) laws, street laws, and regulations must be revised in order to better protect the unarmed and more vulnerable road users and to make the people who are using vehicles with a higher probability of causing injury and death more accountable [60][61][62][63].…”
Section: Planning Cycling For a Sustainable Mobilitymentioning
confidence: 99%
“…The study concluded that familiarity with active transport was important to further increase the use of active transport in the future, and that when the goal is to achieve a higher active mode share, it is important to design targeted transport policies for the identified target group. Furthermore, when wanting to advocate for a certain behavior, it is crucial to first learn about the existing and potential "customers" and collect information about their attitudes and motives (Risser and Sucha, 2020). Rérat (2019) gained insights into the motives and barriers for existing Swiss cyclists (n = 12,031).…”
Section: Previous Researchmentioning
confidence: 99%
“…Среди работ, посвященных изучению внутренних (психологических) детерминант проэкологического поведения в мегаполисе, выделяются исследования, посвященные анализу установок жителей по различным вопросам, связанным с загрязнением окружающей среды, а также характеристик конкретных проэкологичных поведенческих паттернов, которые эти жители используют. К числу таких паттернов, на наш взгляд, относится передвижение на личном или общественном транспорте (Risser, Sucha, 2020).…”
Section: ограничения и перспективы дальнейшего исследованияunclassified